Anti-inflammatory Effect of Apigenin-7-neohesperidoside (Rhoifolin) in Carrageenin-Induced Rat Oedema Model - Omayma A. Eldahshan, Samar S. Azab (Journal of Applied Pharmaceutical Science)
Flavonoids are normal constituents of the human diet and are known for a variety of biological activities. They have been reported to bring benefits in lowering inflammation and oxidative stress. The present investigation was performed first, to evaluate the anti-inflammatory activity of rhoifolin and second, to search for the possible contributing mechanisms for this hypothesized effect. Rhoifolin caused a time and reverse dose dependent reduction of carrageenin-induced rat paw oedema. Following 4 hr of treatment, rhoifolin at doses 2.5, 25 & 250 mg/kg caused a significant inhibition of rat paw edema volume by 14, 25 & 45 % respectively in comparison to the control group (74%). In addition to significantly abrogating prostaglandin E2 level, increasing doses of rhoifolin significantly diminished the TNF-α release in the inflammatory exudates. In the same animal model, rhoifolin increased the total antioxidant capacity in a reverse dose order, with the highest capacity obtained with the lowest dose tested. This study demonstrates for the first time the effectiveness of rhoifolin in combating inflammation in carrageenin-induced rat oedema model.
Keywords: TNF-&alpha; ,prostaglandin E2,Antioxidant capacity.